Human papillomavirus as a single infection in pregnant women from Northeastern Mexico: Cross-sectional study - Bernardo Martínez-Leal; Karla Ivette Álvarez-Banderas; Homero Sánchez-Dávila; Martha Imelda Dávila-Rodríguez; Elva Irene Cortés-Gutiérrez (Shahid Sadoughi University of Medical Sciences, 2020)
Background: The role of human papillomavirus (HPV) as single or multiple infections in pregnant women would be relevant to determine the time to progression and/or the time to regression of cervical lesions.Objective: In this preliminary study, we determined the prevalence of HPV as single or multiple infections in pregnant women from Northeastern Mexico.Materials and Methods: Samples from 31 pregnant and 62 nonpregnant women were examined between January 2015 and November 2015 at UMAE-23 of the Instituto Mexicano del Seguro Social (IMSS). The samples of cervicovaginal exudate were obtained for HPV DNA detection using the INNO-LiPA test, and HPV infections were analyzed as single or multiple infections. Participants completed a questionnaire on sociodemographic, gynecological, obstetric, and sexual behavior characteristics.Results: The mean age of the pregnant women was 25.7 ± 4.8 yr, with an average time of pregnancy of 6 ± 1 months at the time of the study. With respect to age, parity, smoking history, or oral contraceptive use no statistically significant differences between the two studied groups was observed. The HPV infection was 2.7 times higher in pregnant women (35%) than in the control group (13%). In total, 78% of the pregnant women who were HPV-positive presented with single infections compared with 28% of the nonpregnant women.Conclusion: A higher prevalence of HPV as a single infection was found in this sample of pregnant Mexican women. Follow-up is necessary to evaluate the persistence or regression of the infection.